Testing and Analysis of Dynamic Response of a High-Voltage Substation Structure to Short-Circuit Current Forces - Hodgson, Ian; Zorn, Andrew V.; Sause, Richard; Tahmasebi, Ebrahim; Birrell, David; Villani, Luciano; Sagareli, Sergo; Hughes, Martin; Bosworth, MatthewDavid; Graber, Lukas (IEEE transactions on power delivery, 2018)
In substations, buswork, insulators, and supporting structures are subjected to electromagnetic forces caused by short circuits. The current industry design standard of practice is to apply the maximum instantaneous short-circuit force to the structure and perform simple static structural analysis to calculate supporting structure member. However, it is well known that this may be overly conservative since the applied forces and the response of the structure are dynamic in nature. To quantify the dynamic effects, full-scale short-circuit testing was performed on a typical 138 kV disconnect switch stand. The switch stand was instrumented with fiber optic strain gages and subjected to a variety of fault conditions. Extensive dynamic finite element analyses were performed on the subject structure, which were validated with the test data. The results confirm the reduced dynamic response of the structure. With further analyses, it is anticipated that a generalized quasi-static design methodology that considers dynamic response can be developed to replace the present short-circuit design approach.